Backend Programming Techniques in the Development of Resource Manager Features in VRMS Systems Based on ORM Prisma (Program Studi Pendidikan Teknologi Infromasi UMK, 2024)
The development of community makes human resource management in the company also needs to consider changing work rhythms. Nowadays, many companies use external human resources to complete work in the company. Therefore, an external human resource management strategy is needed that suits the company's needs. The Industrial Revolution 4.0 makes human resource management more about cross-generational competency-based management with a more integrated system. Information systems are one of the most widely used technologies in computer science and communication networks in companies' development of computing systems. information system as a primary computing system that needs to be owned by a company in order to optimize the company's business processes. This optimization also includes managing the company's internal and external human resources. This research focused on the development of human resource management systems. Therefore, this system is called the VRMS system. The VRMS system was developed using a hybrid agile method using the concept of Prisma ORM with NestJs. This research succeeded in building a VRMS system with a performance level of 100%.